(untitled) (CIPEEX, 2025)
Introduction: Ulcerative Colitis (UC), highly prevalent in Europe and North America, is a chronic intestinal disease characterized by persistent inflammation. However, its effects are not limited to the gastrointestinal tract; it also impacts biopsychosocial aspects, thereby compromising the quality of life of affected individuals¹. Maintaining a balanced and healthy lifestyle has been shown to alleviate the burden of the disease². Objective: To highlight the importance of lifestyle in patients diagnosed with Ulcerative Colitis. Methodology: This is an integrative review based on four scientific articles. The database used was PubMed. Inclusion criteria comprised publications from the last five years, freely accessible, and available in Portuguese and English. Articles that did not address the central research question — “How does lifestyle impact individuals diagnosed with ulcerative colitis?” — were excluded. Results: Studies demonstrate that a diet high in fat, animal protein, and certain types of fatty acids³, combined with stress, may exacerbate the progression of UC⁴, leading to symptoms such as depression and social withdrawal¹. Furthermore, one study indicated that 70% of participants believed psychosocial stress may have caused or contributed to the worsening of the disease². Thus, lifestyle interventions involving yoga and physical exercise, breath control, proper nutrition, and phytotherapy serve as complementary approaches to pharmacotherapy and have proven effective in improving the patient–disease relationship and managing emotional symptoms. Mind–body integration strategies appear promising in alleviating the distressing conditions associated with UC². Conclusion: Patients diagnosed with UC showed improved prognosis when subjected to multifaceted and individualized interventions focused on lifestyle modification, beyond pharmacological treatment. Nonetheless, further research in this area remains necessary.